The changing context of age-based classification and policy research in the age of subscription-video-on-demand. (1st June 2021) - Cole, Rachel
This article draws on a history of media classification in Australia to consider how this field is developing. The focus is on age-based classification of commercially and professionally produced content, specifically made available through streaming and subscription-video-on-demand (SVOD) platforms. As platform company Netflix steps into the terrain of regulation, this environment is changing quite dramatically. The Netflix tool emerges in a governmental space characterized by new and emerging transnational governance and monitoring Boards, ghost work and moral panics in the form of online firestorms. Questions developed in the time of legacy media that consider human and machine, and industry and government as working separately, are confronted by new practices and points of inquiry with impacts broader than Australian media consumption.